Have the Recent Dynamics of Economic Globalization Biased Social Justice in the European Union? - Caetano, José Manuel (2021)
The literature recognizes that the gradual countries’ involvement in the economic globalization has generated competitive environments that stimulate innovation and economic growth. Yet, globalization has also apparently led to the increase of inequality, contributing for waves of populism and discontent, claiming for justice in sharing these benefits. Thus, it is not surprising that the interaction globalization/ social justice is paying attention to politicians and academics, seeking to identify if there is reason to fear that the globalization leads to increase inequality. This chapter deals with the link between globalization and social justice, measured by updated indicators that improved the data quality and broadened their baseline. In what globalization concerns are applied the renewed KOF index, including de facto and de jure perspectives. Concerning social justice, are used the latest “EU Social Justice Index”. The study reflects on the effects of the recent global financial crises in the EU members, which especially hit the Euro zone.